Turbulent Cascades II Proceedings of the Euromech-ERCOFTAC Colloquium 589 - Gorokhovski, Mikhael; Godeferd, Fabien S. (ERCOFTAC Series, 2019)
Gathering contributions by the most prominent researchers in a highly specialised field, this proceedings volume clarifies selected aspects of the physics of turbulent cascades and their statistical universalities under complex stationary and non-homogeneous conditions. Here, these conditions are induced by the presence of a gas/liquid interface, inertial particles, strong shear, rotation, MHD and stratification. By proposing different ways to model turbulence effects under these complex conditions, the book will be of considerable interest not only to academic researchers, but also to specialists and junior researchers in the domain of propulsion and power, as well as those whose work involves various applications related to atmospheric, oceanic and planetary physics.